Long noncoding RNA GAS5: a novel marker involved in glucocorticoid response. - Lucafo, M; De Iudicibus, S; Di Silvestre, A; Pelin, M; Candussio, L; Martelossi, S; Tommasini, A; Piscianz, E; Ventura, A; Decorti, G (Curr Mol Med, 2015)
Glucocorticoids (GCs) exert their effects through regulation of gene expression after activation in the cytoplasm of the glucocorticoid receptor (GR) encoded by NR3C1 gene. A negative feedback mechanism resulting in GR autoregulation has been demonstrated through the binding of the activated receptor to intragenic sequences called GRE-like elements, contained in GR gene. The long noncoding RNA growth arrest-specific transcript 5 (GAS5) interacts with the activated GR suppressing its transcriptional activity. The aim of this study was to evaluate the possible role of GAS5 and NR3C1 gene expression in the antiproliferative effect of methylprednisolone in peripheral blood mononuclear cells and to correlate the expression with individual sensitivity to GCs. Subjects being poor responders to GCs presented higher levels of GAS5 and NR3C1 in comparison with good responders. We suggest that abnormal levels of GAS5 may alter GC effectiveness, probably interfering with the mechanism of GR autoregulation.
Keywords: Adult; Cell Proliferation; Female; Gene Expression Regulation; Glucocorticoids; Humans; Leukocytes, Mononuclear; Male; Methylprednisolone; Middle Aged; Receptors, Glucocorticoid; RNA, Long Noncoding; Transcription, Genetic

Prevalence of celiac disease in patients with severe food allergy. - Pillon, R; Ziberna, F; Badina, L; Ventura, A; Longo, G; Quaglia, S; De Leo, L; Vatta, S; Martelossi, S; Patano, G; Not, T; Berti, I (Allergy, 2015)
The association between food allergy and celiac disease (CD) is still to be clarified. We screened for CD 319 patients with severe food allergy (IgE > 85 kU/l against food proteins and a history of severe allergic reactions) who underwent specific food oral immunotherapy (OIT), together with 128 children with mild allergy who recovered without OIT, and compared the prevalence data with our historical data regarding healthy schoolchildren. Sixteen patients (5%) with severe allergy and one (0.8%) with mild allergy tested positive for both genetic and serological CD markers, while the prevalence among the schoolchildren was 1%. Intestinal biopsies were obtained in 13/16 patients with severe allergy and in the one with mild allergy, confirming the diagnosis of CD. Sufferers from severe food allergy seem to be at a fivefold increased risk of CD. Our findings suggest that routine screening for CD should be recommended in patients with severe food allergy.

Letter: TPMT activity and age in IBD patients. - Stocco, G; De Iudicibus, S; Cuzzoni, E; Decorti, G; Martelossi, S; Ventura, A (Aliment Pharmacol Ther, 2012)
Keywords: Azathioprine; Humans; Immunosuppressive Agents; Inflammatory Bowel Diseases; Thioguanine

Upper gastrointestinal involvement in paediatric onset Crohn's disease: prevalence and clinical implications. - Crocco, S; Martelossi, S; Giurici, N; Villanacci, V; Ventura, A (J Crohns Colitis, 2012)
BACKGROUND AND AIMS: Our study evaluated the prevalence, the characteristics and implications of the upper gastrointestinal localisation (UGI+) in paediatric Crohn's Disease (CD) patients. METHODS: This prospective study evaluated 45 newly diagnosed CD patients at diagnosis and follow up with respect to CD localisation. RESULTS: All patients presented CD at the colon and/or ileum. In 24/45 patients (53.3%, 12 F and 12 M) an UGI+ involvement was also found. UGI+ patients had a younger age of onset (10.9 years versus 12.6 years; P<0.05). PCDAI at diagnosis was significantly higher in the UGI+ (41 vs. 25 P<0.01). UGI+ patients were overall more symptomatic. Pancolitis and extraintestinal manifestations were also more frequent (19/24 (80%) vs. 12/21 (57%) P<0.01). Growth was more impaired at diagnosis in UGI+ patients. By the end of the follow-up (mean 3 years, range 2 to 4) no significant difference was found in PCDAI (17 in UGI+ patients vs. 11 in UGI- P=NS), or the number of relapses. Weight and growth catch-up in UGI+ patients were comparable to UGI- ones. However, UGI+ patients required a more aggressive therapeutic approach. CONCLUSION: At least half of paediatric onset CD patients have an upper gastrointestinal localisation. UGI+ patients present an earlier onset and a more severe disease. The final outcome does not differ, but UGI+ patients require a more aggressive therapeutic approach.
Keywords: Adolescent; Age of Onset; Child; Crohn Disease; Female; Humans; Male; Prospective Studies; Upper Gastrointestinal Tract